2019
DOI: 10.12659/ajcr.915453
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Features of a Myeloid Sarcoma of the Breast as a Relapse of Acute Myeloid Leukemia After Stem-Cell Transplantation: A Case Report

Abstract: Patient: Female, 24 Final Diagnosis: Myeloid sarcoma of the breast Symptoms: Breast lump Medication: — Clinical Procedure: Core needle biopsy Specialty: Radiology Objective: Rare disease Background: Myeloid sarcoma is a rarely observed extramedullary presentation of myeloid leukemia that seldom manifests in the breast. Myeloid sarcoma can occur before, concurrently with, or fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Mammogram findings previously described include large, noncalcified irregular masses with poorly defined margins [11] , [12] , [13] , [14] . US findings are variable and include homogeneous or heterogeneous hypoechoic lesions that are hypervascularized on color Doppler scans and cannot be easily distinguished from benign lesions [ [15] , [16] , [17] ]. Additionally, MRI can be a valuable diagnostic tool with breast MS presenting as hypointense lesions on T1-weighted images, hyperintense on T2-weighted images, and with inhomogeneous enhancement [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Mammogram findings previously described include large, noncalcified irregular masses with poorly defined margins [11] , [12] , [13] , [14] . US findings are variable and include homogeneous or heterogeneous hypoechoic lesions that are hypervascularized on color Doppler scans and cannot be easily distinguished from benign lesions [ [15] , [16] , [17] ]. Additionally, MRI can be a valuable diagnostic tool with breast MS presenting as hypointense lesions on T1-weighted images, hyperintense on T2-weighted images, and with inhomogeneous enhancement [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bubulac et al [ 19 ] reported a 30-year-old female diagnosed with AML-M4 who achieved complete remission after chemotherapy and subsequently underwent allo-SCT for consolidation. After 5 months, the patient presented with right breast tumors resulting from AML relapse with breast MS. Another recent study [ 13 ] reported MS of the breast as a relapse of AML after stem-cell transplantation. In 2018, Cheng et al [ 20 ] presented the case of a 46-year-old woman with a known history of AML who had bilateral breast masses with pain and itchiness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of breast imaging for the initial assessment of the disease, this technique lacks specificity, and MS can mimic several other tumors, including breast carcinoma and lymphoma. Moreover, only a few reports on breast MS have been published to date [ 13 – 16 ]. Currently, only histological examination with IHC can be used to confirm the diagnosis of breast MS [ 7 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most breast masses are hyperdense, have a rounded shape and microlobulated margins, and occasionally accompany internal microcalcifications. On ultrasound, they usually present as solitary or multiple masses that tend to be homogeneously hypoechoic with microlobulated or indistinct margins 2 . The immunohistochemical study is extremely useful in recognizing MS, the most specific markers of myeloid differentiation being myeloperoxidase and lysozyme, both positive in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Other synonyms are granulocytic sarcoma and extramedullary myeloid tumor 1 . Although it can affect any region of the body, its presentation in the breast is extremely uncommon, having been, until 2005, only 67 cases recorded in the literature 2 , with additional episodes reported sporadically until recently 3 . Skin, lymph nodes, gastrointestinal tract, bone, soft tissues and testicles are the most frequent sites of involvement 4 .…”
Section: Introductionmentioning
confidence: 99%